Analisis Peran Manfaat Pajak Tangguhan dalam Mitigasi Kerugian pada PT KAI (Persero) Tahun 2020–2021 - Diyan Rifqiyah; Fortunata Aurelia Natasia Djagong; Rara Nur Aryani; Varadila Zahra (Jurnal Bisnis Kreatif dan Inovatif, 2025)
The COVID-19 pandemic significantly affected the financial performance of PT Kereta Api Indonesia (Persero), as reflected in the shift from profit in 2020 to a substantial pre-tax loss in 2021. This change had direct implications for the company’s tax components, particularly current tax and deferred tax, in accordance with PSAK 46 on Income Taxes. This study aims to analyze the changes in current tax and deferred tax between the two reporting periods and to examine the role of deferred tax benefits in reducing the company’s net loss. The research employs a quantitative descriptive approach with a comparative analysis method using secondary data from the company’s interim consolidated financial statements. The findings indicate that in 2021 the company recognized a deferred tax benefit that converted total income tax into a net tax benefit, thereby reducing the company’s net loss by approximately 15.8 percent. These results demonstrate that deferred tax does not merely arise from temporary differences but can function as an instrument of loss mitigation during periods of financial distress. The implications of this study highlight the importance of accurate application of PSAK 46, especially in times of economic downturn, and emphasize the need for realistic assessments of future taxable profits to ensure the reliability of deferred tax asset recognition.